Book Reviews (The Muslim world, 1952)
Submission in Suffering and other Essays in Eastern Thought. By H. H. Rowley. This is the Way: Prayers and Precepts from World Religions. Chosen by Jesse Orton Jones. The World Through Literature. Ed. by Charlton Laird. The Birth of Civilization in the Near East. By Henri Frankfort. History of the Arabs, From the Earliest Times to the Present. By Philip K. Hitti. South Arabian Poetry, I: Prose and Poetry from Hadramaut. Edited, collated and corrected, with an introductory Preface, by R. B. Serjeant. Ibn Khaldun and Tamerlane. By Walter J. Fischel. Tunisie. By Pierre Hubac. Paris, Editions Berger-Levrault. The Near East and the Great Powers. Edited by Richard N. Frye. The Persian Language. By Reuben Levy. A Medical History of Persia and the Eastern Caliphate From Earliest Times Until the Year A.D. 1932. By Cyril Elgood, M.A., M.D., F.R.C.P. Kashir: Being a History of Kashmir, From the Earliest Times to Our Own, By G.M.D. Sufi